In the lonely hours - Morgan, Shannon (Kensington Books, 2024)
"On a small island in a remote corner of northwest Scotland lies Maundrell castle, owned by its wealthy namesake family for centuries - until now. Edwina Nunn is shocked to learn a relative she never heard of has bequeathed the castle and its land to her. What awaits Edie and her teenage daughter, Neve, is even more startling, for the castle is home to a multitude of ghosts. Yet there’s a strange beauty in the austere architecture and the eerie, bloody waters of Loch na Scáthanna, the Lake of Shadows. Beguiled by a frightened ghost who gazes longingly out of the castle’s windows, Edie and Neve are drawn to the legends shrouding the island and the mystery of the Maundrell Red - a priceless diamond that disappeared decades before. Is the gem really cursed, and the cause of the family tragedies that have all occurred on Samhain - Scottish Halloween? As Samhain approaches once more, Edie and Neve race to peel back the dark secrets entwining the living and the dead - a twisted story of bitter cruelty and hidden love - or they will become another Maundrell tragedy trapped in the lonely hours..." -- Back cover.